A Double-Key Based Encryption-Decryption Process for Stronger Secured Message Transactions (GUB Journal of Science and Engineering, 2020)
A double-key based stronger secured electronic message transaction system has been designed and developed using Python programming language by performing encryption-decryption process. To do this, simple cryptographic encryption and decryption techniques are used with two keys avoiding vulnerabilities of a single key. First, the intended message is encrypted with the private key of sender (PRa) and the output is again encrypted with a shared secret key (K1) that generates ciphertext. The output ciphertext is again encrypted with another shared secret key (K2) that generates a code that serves as Message Authentication Code (MAC), which is concatenated with the ciphertext. And again encrypted them with shared secret key K1 that produced final ciphertext which is to be send to the intending recipient. The shared secret keys K1 and K2 are getting from the key distribution center (KDC). In the receiving end, receiver first decrypts the received information with the shared secret key K1 that gives the ciphertext and MAC of the ciphertext, and then decrypts only the MAC to generate a new ciphertext′and compare the new ciphertext′ with the received ciphertext that ensures the ciphertext authentication as well as message authentication; if ciphertexts are found same, then the ciphertext is decrypted with shared secret key K2 and again is decrypted with the sender’s public key (PUa) and retrieve the message; otherwise discarded. This proposed system ensures the stronger authenticated message transactions among the communicants. Finally, a comparative study with the existing systems has also been performed and measured stronger security. This technique can be applied for any secured electronic information transfer system with stronger security services.GUB JOURNAL OF SCIENCE AND ENGINEERING, Vol 6(1), Dec 2019 P 75-80